Study of Various Prognostic Factors Affecting Successful Myringoplasty in a Tertiary Care Centre - Dangol,Kripa (2017)
Abstract Introduction Myringoplasty is a commonly performed otologic surgery. Objectives The objective of this study is to evaluate the effect of prognostic factors like - size, site of perforation, status of operating ear, approach, status of contralateral ear, experience of surgeon, primary or revision myringoplasty, and smoking in graft uptake, as well as to evaluate the hearing results after myringoplasty. Methods This is a prospective study. We included in our sample patients aged over 13 years with a Tubotympanic Chronic Otitis Media diagnosis. The patients underwent preoperative evaluation and Pure Tone Audiogram within one week prior to surgery.We performed myringoplasty using temporalis fascia graft with conventional underlay technique. We evaluated postoperative graft uptake and various factors related to the study and did a Pure Tone Audiogram at one year after surgery. Results The graft uptake rate after myringoplasty was 83.1% at one year in 219 patients. Graft uptake with normal opposite ear was 88.2%, and with Tubotympanic Chronic Otitis Media was 75% (statistically significant). We found no statistically significant difference in graft uptake results with other factors. We calculated hearing results of 132 patients with normal ossicular status who underwent myringoplasty. The average Air Conduction Threshold improvement was 11.44dB (p < 0.001) and the average Air-Bone Gap closure was 8.89dB, highly statistically significant (p < 0.001). Conclusion Diseased contralateral ear was a statistically significant poor prognostic factor for graft uptake after myringoplasty. Other factors studied were not statistically significant determining factor for graft uptake. Hearing improves significantly after myringoplasty if the ossicles are normal.